PENGEMBANGAN KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR MELALUI METODE DISKUSI KELOMPOK - Puspitasari, Alwanda Dwi (Universitas Sulawesi Tenggara, 2023)
Developing speaking skills in elementary school students is very important to support their communication skills in the future. One effective method to train these skills is the group discussion method, which allows students to interact, express their opinions, and listen to the opinions of others. This study aims to examine the effectiveness of the group discussion method in improving elementary school students' speaking skills. This literature study collects and analyzes the results of relevant previous studies to understand how this method is applied and its impact on the development of students' speaking skills. The results of this literature study indicate that group discussions can improve students' self-confidence, critical thinking skills, and speaking abilities.